Assesses The Green Infrastructure - Jasim, Ihsan Abbass (Iraqi Journal of Architecture and Planning, 2017)
The Problems increase dramatically day after day in cities and declining quality of life, Resulting the decline on ecosystems, To address the problems in an integrated manner infrastructure green concepts emerged in the nineties of the last century and spread throughout the world, but there seems to be lack of understanding of green infrastructure in Iraq, as well as the weakness of environmental awareness and the important role of biodiversity for human life, Therefore, the search is trying to address the knowledge gap of this concept, as well as the development of strategies for the development in the city of Kut, through an integrated a comprehensive approach and not as parts individually guidance of the concept of infrastructure Green to take advantage of the banks of rivers and water resources that most Iraqi cities by the fall, to take advantage of the water sources including in harmony with the principles of green infrastructure. The research found that there is a shortage and poor distribution of green areas in the city of Kut, not to take advantage of the city characterized by an abundance of water resources in the promotion of green areas and invested for the establishment of an effective green infrastructure site. Search integrated strategies for the development of green infrastructure in the city has also developed in line with the site and the privacy of the city of Kut.